Sweet syndrome: a sweet disease with a bitter diagnosis - Ganti, Eswar; Pinnamaneni, Shalima; A., Santhosh Kumar; K., Syam Venkat (International Journal of Research in Medical Sciences, 2018)
Sweet syndrome is an acute febrile neutrophilic dermatosis first described by Robert Douglas Sweet in 1964. Sweet syndrome presents in three clinical settings: classical (or idiopathic), malignancy-associated, and drug-induced. It has been associated with hematopoietic malignancies and myelodysplastic disorders. A-28-years married woman presented to us with chief complaints of Fever and Multiple swellings over the body since 2 months. At presentation she has Pallor; venous hum present. Multiple, tender, erythematous subcutaneous swellings, firm in consistency noted in both forearms. Skin over the swellings is pinchable; superficial skin is normal. Sweet syndrome can occasionally cause an intense systemic response involving the lungs, liver and musculoskeletal system. The skin lesions in Sweet syndrome typically start as erythematous papules, plaques, and nodules. The lesions can take on pseudovesicular or pseudopustular appearance, and sometimes fully formed vesicles or pustules develop. The lesions can be subcutaneous mimicking erythema nodosum which can’t be differentiated unless a biopsy is taken. Because the diagnosis of Sweet syndrome can be challenging, particularly when associated with other connective tissue disorders such as SLE, a set of diagnostic criteria were proposed initially by Su and Liu and then revised by Von den Driesch. The diagnosis is based upon the presence of two major and two of the four minor criteria. Concurrent Sweet syndrome and SLE are exceedingly rare. Twelve patients with both Sweet syndrome and systemic lupus erythematosus (SLE) have been previously reported. We report a case of sweet syndrome associated with SLE diagnosed in our hospital. In our patient, diagnostic criteria are satisfied for Sweet syndrome as well as for SLE (ACR criteria-patient had polyarthralgia, anemia, thrombocytopenia, ANA and Ds DNA positive. Four out of 11 are fulfilled for SLE). Patient responded to corticosteroids.